2011
DOI: 10.1159/000323840
|View full text |Cite
|
Sign up to set email alerts
|

Common Polymorphisms in <i>KNCJ5</i> Are Associated with Early-Onset Lone Atrial Fibrillation in Caucasians

Abstract: Objectives: The aim of this study was to screen lone atrial fibrillation (AF) patients for mutations in the genes KCNJ2, KCNJ3 and KCNJ5, all encoding potassium channels. Furthermore, we wanted to replicate the prior association of two single-nucleotide polymorphisms (SNPs) in KCNJ5, C171T (rs6590357) and G810T (rs7118824), with lone AF in Han Chinese. Methods: We sequenced the coding region and splice site of KCNJ2, KCNJ3 and KCNJ5 in 187 early-onset lone-AF patients screening for mutations and counting SNP f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Control groups I and II were previously described in detail. 26,27 These control groups were used in the genotyping of rs6795970 using a Taqman assay. To increase the statistical power of our association study, we also used a third control cohort (control group III), comprising 6,161 individuals randomly selected from a Danish cohort study (Inter99, LuCamp).…”
Section: Methodsmentioning
confidence: 99%
“…Control groups I and II were previously described in detail. 26,27 These control groups were used in the genotyping of rs6795970 using a Taqman assay. To increase the statistical power of our association study, we also used a third control cohort (control group III), comprising 6,161 individuals randomly selected from a Danish cohort study (Inter99, LuCamp).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies link GIRK1 to schizophrenia susceptibility in a Chinese population; 13 in this study, lower GIRK1 expression levels in post-mortem brains from schizophrenic and bipolar individuals were observed. Other studies have suggested GIRK2 and GIRK3's involvement in responsiveness to analgesics, 14,15 GIRK2's potential link to alcoholism, 16 as well as links between GIRK4 and early onset atrial fibrillation 17 and hyperaldosteronism. 18 Although GIRKs have long been the focus of basic research efforts providing mounting evidence to linkages to human disease, there are very few pharmacological tools that have been reported 19 that might allow a better understanding of the roles of GIRKs in normal and pathophysiological conditions.…”
Section: −3mentioning
confidence: 97%
“…76 An association between early-onset AF and 2 common polymorphisms in KCNJ5 has been reported. 77 However, since neither polymorphism results in an amino acid change, the implications of this finding are unclear. Mice with genetic ablation of Kir3.1 or Kir3.4 are viable and lack any I KACh current.…”
Section: Kir21mentioning
confidence: 99%